PENGARUH PENERAPAN STRATEGI PEMBELAJARAN KOOPERATIF TIPE PAIR CHECKS TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS XI IPA SMAN 1 2x11 ENAM LINGKUNG - Silvia, Berly; Rismen, Sefna; Aima, Zulfitri (Pendidikan Matematika, 2013)
TheÂ  backgroundsÂ  ofÂ  thisÂ  researchÂ  areÂ  theÂ  studentsâÂ  unwillingnessÂ  toÂ  shareÂ  the informationÂ  andÂ  theÂ  styudentsâÂ  lowÂ  conceptÂ  understandingÂ  onÂ  theÂ  mathematical learning of the grade-XI natural-science class of SMAN 1 2x11 Enam Lingkung inÂ  theÂ  yearsÂ  2012/2013. TheÂ  typeÂ  ofÂ  researchÂ  isÂ  experimentalÂ  byÂ  using Randomized Control Group Only Design. The data analysis technique used is TTest . Techniques of data analysis were performed using one-way t test. Based on the analysis of data obtained t of 4.95 is greater than the amount specified t table 1.64.Â  Then theÂ  hypothesisÂ  inÂ  thisÂ  researchÂ  received.Â  InÂ  conclusion,Â  studentsâ comprehension of math concept that apply cooperative learning Pair Checks than studentsâ comprehension of math concept that apply conventional learning.